Working conditions of strength and conditioning coaches in New Zealand and the Pacific Islands. - Jones, B. W.; Humphrey, R. A.; Ramsey, C. A.; Middlemas, S.; Spencer, K. (Journal of Australian Strength and Conditioning, 2020)
The strength and conditioning coach (SCC) is a sports service provider that plays an integral role in preparing an athlete for competition. The bio-physical elements of strength and conditioning are well-known, however little information is available on the working conditions of SCCs. An online, in-depth, survey was used to gather quantitative data from coaches within New Zealand and the Pacific Islands (NZP). Participants were categorised into the three most common employment styles for this population, (1) permanently employed, (2) self-employed and (3) other-employed in order to compare responses. 72 coaches from New Zealand (n = 67) and the Pacific Islands (n = 5) responded to the survey. Findings revealed the working conditions of SCCs within this region vary and depend on the style of employment. Those employed permanently had the greatest industry experience (mean = 8.69 years), have a tertiary level qualification (100%) and hold or are working towards gaining an industry-specific accreditation (85.18%). They receive higher remuneration (mean = $67,687.86NZD), have benefit packages (77.77%) and work longer hours than self-employed and other-employed coaches (p < 0.05). Permanent employment appears to be the most rewarding form of employment for coaches in this region, however it does not come without difficulties relating to work conditions. These challenges include travelling away from home, 10+ hour days and hours that frequently exceed contracted expectations. Theoretically, this research provides preliminary data for coaches working within this region and builds upon the research for this topic globally. This research allows for early-career SCCs to make informed professional development and career-related decisions.